The RSF1 histone-remodelling factor facilitates DNA double-strand break repair by recruiting centromeric and Fanconi Anaemia proteins. - Fabio Pessina; Noel F Lowndes (PLoS Biology, 2014)
ATM is a central regulator of the cellular responses to DNA double-strand breaks (DSBs). Here we identify a biochemical interaction between ATM and RSF1 and we characterise the role of RSF1 in this response. The ATM-RSF1 interaction is dependent upon both DSBs and ATM kinase activity. Together with SNF2H/SMARCA5, RSF1 forms the RSF chromatin-remodelling complex. Although RSF1 is specific to the RSF complex, SNF2H/SMARCA5 is a catalytic subunit of several other chromatin-remodelling complexes. Although not required for checkpoint signalling, RSF1 is required for efficient repair of DSBs via both end-joining and homology-directed repair. Specifically, the ATM-dependent recruitment to sites of DSBs of the histone fold proteins CENPS/MHF1 and CENPX/MHF2, previously identified at centromeres, is RSF1-dependent. In turn these proteins recruit and regulate the mono-ubiquitination of the Fanconi Anaemia proteins FANCD2 and FANCI. We propose that by depositing CENPS/MHF1 and CENPX/MHF2, the RSF complex either directly or indirectly contributes to the reorganisation of chromatin around DSBs that is required for efficient DNA repair.